Demographic and economic determinants of housing demand in the Johannesburg metro - Sebogoane, Nkgadi Frederick (My University, 2019)
Housing forms a large part of household wealth and expenditure, it therefore follows that any change in housing markets, whether positive or negative, will have a direct impact on the wealth and expenditure of households. Numerous studies have researched housing demand for developed countries but applied research for developing countries is still relatively scarce, more so in South Africa. This study seeks to investigate the determinants of residential real estate demand in the Johannesburg metro. The research employs a mix of descriptive, correlation, and regression techniques, descriptive and correlation analyses are used to explore the basic features of the data that is used in the research. Regression techniques extend the descriptive and correlation analysis in estimating regression coefficients that measure how explanatory variables influencing housing demand, whether positively or negatively. The research found that, in the Johannesburg Metro context, after controlling for most of the variables in a housing model as we formulated and estimated, the effect of increasing the price at which exemption of transfer duty is applied is more effective in increasing housing demand in the low-income, middle- and high-income classes in that order.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Property Development and Management to the School of Construction, Economics and Management, Faculty of Science, University of the Witwatersrand, 2019
Keywords: Housing policy--South Africa; Low-income housing--South Africa